Chloroform fraction of ethanolic extract of Elephantopus scaber Linn. increase the p53 expression on human breast cancer (T47D) cell line - Mahfudh, Nurkhasanah; Sulistyani, Nanik; Mahdi, Lukman (Universitas Ahmad Dahlan, 2017)
Elephantopus scaber Linn had been used as traditional medicine. It contain some lacton sesquiterpene with antiproliferative activity. The study aim was to explore the effect of chloroform fraction of ethanolic extract of E.scaber on the expression of p53 on T47D cell line. The ethanol extract was found by maceration method. The extract was then fractionated using petroleum ether and chloroform respectively to get the chloroform fraction. The expression of p53 was observed by immunocytochemistry method with antip53 antibody. The p53 cell line was cultured and treated with fraction with concentration of 7.06 and 3.53 µg/ml. The expression of p53 was showed by brown colour in the nucleus of the cell. The result showed that chloroform fraction treatment with concentration of 7.06 µg/ml induced apoptotic cell death in the end stage (necrosis). While the treatment with lower concentration 3.53 µg/ml could increase the p53 expression.